The impact of carbon trading on industry: Evidence from German manufacturing firms - Sebastian Petrick; Ulrich J. Wagner (Kiel Institute for the World Economy (IfW), 2014)
We estimate the causal impact of the EU Emissions Trading Scheme on manufacturing firms using comprehensive panel data from the German production census. Semiparametric matching estimators yield robust evidence that the policy caused treated firms to abate onefifth of their CO2 emissions between 2007 and 2010 relative to non-treated firms. This reduction was achieved predominantly by improving energy efficiency and by curbing the consumption of natural gas and petroleum products, but not electricity use. We find no evidence that emissions trading lowered employment, turnover or exports of treated firms.
Keywords: 330